2011
DOI: 10.5272/jimab.2011171.130
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Adenosine Deaminase Serum Concentrations in the Diagnosis of Extra-Pulmonary Tuberculosis

Abstract: Extra pulmonary tuberculosis (EPTB) is a growing problem worldwide. Due to the nature of the disease, the diversity of clinical pictures as well as its minor epidemiological importance, the diagnosis is difficult and often late.In addition to standard TB diagnostic techniques use of new biochemical (surrogate markers) are increased.With this work we wanted to examine the usefulness of serum adenosine deaminase levels as a diagnostic parameter for EPTB.The work included 116 patients with fever of unknown origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
1
7
1
Order By: Relevance
“…The commonest pattern in this study was pattern B (66.34% cases) showing epithelioid granuloma with necrosis. The same was observed by Bhattacharya et al[18] and Khanna et al[19] in 69.4% and 50.5% cases, respectively.Results similar to our study were also demonstrated in the studies by Sulakshana et al[21], Ahmed et al[22], Abdelsadek et al[23], Mugulkod et al[15], and Stevanovic et al[3]. This was in contrast to the findings of Conde et al[22].…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The commonest pattern in this study was pattern B (66.34% cases) showing epithelioid granuloma with necrosis. The same was observed by Bhattacharya et al[18] and Khanna et al[19] in 69.4% and 50.5% cases, respectively.Results similar to our study were also demonstrated in the studies by Sulakshana et al[21], Ahmed et al[22], Abdelsadek et al[23], Mugulkod et al[15], and Stevanovic et al[3]. This was in contrast to the findings of Conde et al[22].…”
supporting
confidence: 92%
“…In 1993, TB was declared as a public health emergency on a global level by WHO [2]. Depending upon the locus of involvement, TB can have two different manifestations clinically: Pulmonary TB, wherein infection is situated in the lungs and Extrapulmonary TB, involving any site other than the lungs, for example, abdomen, lymph nodes, meninges, skin, or genito-urinary tract [3]. The most common manifestation of mycobacterial extra-pulmonary disease is the involvement of peripheral lymph nodes, usually of the cervical area [4].…”
Section: Introductionmentioning
confidence: 99%
“…Activity of this enzyme increases in TB patients. In some studies, the level of ADA in sputum and serum was used for diagnosis of TB, and it was monitored during TB treatment (Afrasiabian et al,2013;Stevanovic et al, 2011).…”
Section: Management Of Chylous Ascitesmentioning
confidence: 99%
“…Accordingly, there develops tests based on biochemical response of body towards TB infection. Adenosine deaminase (ADA) test is one of biochemical test for TB (Stevanovic et al, 2011;Ninghot et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies have proved its value in TB diagnosis, even for assessing TB effusions in which activity of this enzyme increases in the infected patients 7 .In some studies, the level of ADA in body fluids and serum was used for diagnosis of TB and it was monitored during TB treatment 8 . Initial studies used effusion fluids and a very limited number of studies used patients' serum 9 . Since, it is not always possible to access effusion liquids everywhere in pulmonary and extra pulmonary TB; therefore, it would be helpful to take advantage of serum levels.…”
mentioning
confidence: 99%